Analysis of Portable DC to DC Solar Power Supply - Hayadin, Muhammad Nur Razin; Saiman, Suhaimi (Evolution in Electrical and Electronic Engineering, 2022)
This paper presents the analysis process of a small-scale, cost-effective portable solar power supply. Photovoltaics or PV for the short term is a type of renewable energy that has lately gained popularity in modern technology. The demand for future work is for great efficiency, reliability, and low cost. PV charge controllers that are small enough to carry about have become highly common in PV systems. PV systems typically include a photovoltaic array, charge controller, rechargeable battery, and DC load. In a PV system, the charge controller is important. PV is often acknowledged as one of the most environmentally beneficial and widely available alternative energy sources. A solar panel is included in the final product to convert solar energy to electrical energy. The electrical energy was stored in a rechargeable battery that was regulated by a solar charge controller. To keep track of the battery storage capacity, a battery level indicator was shown on the controller. A solar charge controller is built to cut down the maximum output of an 18 V DC voltage solar panel to a regulated 12 V DC power supply for charging handheld devices such as smartphones and tablets and as well as a DC power supply source.